Fabrication of hydrophobic compressed oil palm trunk surface by sol-gel process - Syafiqah, Muzakir; Nurjannah, Salim; Nurul Huda, Abu Bakar; Rasidi, Roslan; Lim, Wan Sin; Rokiah, Hashim (IOP Publishing, 2018)
Improvement of the robustness of hydrophobic surfaces is crucial to achieving commercial applications of these surfaces in such various areas as self-cleaning, water repellency and corrosion resistance. Compressed oil palm trunk (OPT) panel is one of potential product which can be used as panelling and indoor furniture application. By adding hydrophobic properties to compressed oil palm trunk panel might increase the application of compressed oil palm trunk especially for outdoor application. In this study, fabrication is using the sol-gel technique. Sol-gel was prepared by adding ethanol with Hexadecyl Trimethyl Ammonium Bromide (CTAB) solution with Tetraethyl Orthosilicate (TEOS) with surface modification of chlorotrimethylsilane (CTMS). The surface with hydrophobic coating was undergone surface analysis with contact angle machine with the aid of software SCA 20 and the determined of the morphology of surface with scanning electron microscope (SEM). The produced compressed oil palm trunk surfaces exhibited promising hydrophobic properties with a contact angle of 104° and the relatively better mechanical robustness.